Cardiovascular testing recovery in Latin America one year into the COVID-19 pandemic: An analysis of data from an international longitudinal survey - Luca Bremner; Joao Vitola; Rodrigo Cerci; Roxana Campisi; Raúl Araujo Ríos; Teresa Massardo; Claudia Gutierrez-Villamil; Felix Solis; Amalia Peix; Herwin Speckter; Mayra Sanchez Velez; Ana Camila Flores; et al. (International Journal of Cardiology: Heart & Vasculature, 2024)
Background: The COVID-19 pandemic disproportionately impacted Latin America (LATAM), significantly disrupting cardiovascular testing. This study evaluated cardiac procedure recovery in LATAM one year after the outbreak. Methods: The International Atomic Energy Agency (IAEA) surveyed 669 centers in 107 countries worldwide, including 135 facilities in 19 LATAM countries, to assess cardiovascular procedure volumes in March 2019, April 2020, and April 2021, and changes in center practices and staffing conditions one year into the COVID-19 pandemic. Findings: LATAM centers reported a 21 % decrease in procedure volumes in April 2021 from pre-pandemic-baseline, vs. a 0 % change in the rest of the world (RoW), and greater volume reductions for almost all procedure types. Centers in Central America and Mexico reported the largest procedure reductions (47 % reduction) compared to the Caribbean (15 %), and South America (14 %, p = 0.01), and this LATAM region was a significant predictor of lower procedure recovery in multivariable regression. More LATAM centers reported reduced salaries and increased layoffs of clinical staff compared to RoW, and LATAM respondents estimated that half of physician and non-physician staff experienced excess psychological stress related to the pandemic, compared to 25 % and 30 % in RoW (p < 0.001). Conclusions: Cardiovascular testing recovery in LATAM trailed behind RoW for most procedure types, with centers in Central America and Mexico reporting the greatest volume reductions. This study found lasting impacts of COVID-19 on cardiovascular care in LATAM and the need for mental health support for LATAM healthcare workers in current and future pandemics.